2016
DOI: 10.1002/er.3622
|View full text |Cite
|
Sign up to set email alerts
|

Study of the photon down-conversion effect produced by thin silicon-rich oxide films on silicon solar cells

Abstract: Summary In the present work, we studied the photon down‐conversion effect produced by thin films of silicon oxide with embedded silicon nanocrystals also called silicon‐rich oxide (SRO). These films have been used to absorb high energy light and the re‐emission of two or more low energy photons (~1.1 eV) with the goal of improving the external quantum efficiency and consequently the conversion efficiency of silicon solar cells. According to our results, the incorporation of a thin SRO film on the solar cell su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Later, SiN x :Tb 3+ -Yb 3+ , and silicon-rich oxide have also been proposed as DC materials for silicon solar cells. [89,90] Recently, Yao et al reported the Tb 3+ -Yb 3+ co-doped NaYF 4 nanoparticles (NPs) as DC material for silicon solar cells. [91] Figure 4D shows the J-V F I G U R E 3 (A) Air mass (AM) 1.5G spectrum, showing the fraction (highlighted in black) absorbed by a Si-based PV cell.…”
Section: Materials For Inorganic and Dssc Solar Cellsmentioning
confidence: 99%
“…Later, SiN x :Tb 3+ -Yb 3+ , and silicon-rich oxide have also been proposed as DC materials for silicon solar cells. [89,90] Recently, Yao et al reported the Tb 3+ -Yb 3+ co-doped NaYF 4 nanoparticles (NPs) as DC material for silicon solar cells. [91] Figure 4D shows the J-V F I G U R E 3 (A) Air mass (AM) 1.5G spectrum, showing the fraction (highlighted in black) absorbed by a Si-based PV cell.…”
Section: Materials For Inorganic and Dssc Solar Cellsmentioning
confidence: 99%
“…After 180 min of thermal treatment a small intensity appears in the films from blue to red regions, as shown in Figure 2b. The above is due to the long thermal treatment, which is enough for the formation of agglomerations of the small silicon excess, creating the defects and silicon clusters that cause the luminescence as explained in [4]. However, the PL intensity of the SRO45 film is practically negligible in order to be used as a photon converter film in a photodetector.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Si-NCs embedded in a dielectric matrix have been proved as a functional active material for light-emitting devices and photodetectors [3,[6][7][8]. Moreover, Si-NCs have been used to increase the efficiency of Si-based solar cells through the photon down-conversion phenomenon [6,9]. Therefore, Si-NCs could allow for the development of Si-based photonic devices [10].…”
Section: Introductionmentioning
confidence: 99%